Are the neglected tropical diseases under control in the tri-border region between Brazil, Argentina, and Paraguay? - Filipa Mendes Oliveira; Ricardo Arcêncio; Marcos Augusto Moraes Arcoverde; Inês Fronteira (Journal of Infection in Developing Countries)
Introduction: Implementation of prevention and control measures for communicable diseases in border regions can be challenging and lead to inefficient attempts to control them. We describe evidences on the strengths, weaknesses, opportunities and challenges regarding implementation of health interventions for control, prevention and treatment of selected neglected tropical diseases (NTD), a group of transmissible diseases typically prevalent in tropical countries and vulnerable populations, in the tri-border between Brazil, Argentina, and Paraguay.